The Influence of Aviation Security Unit Performance on the Quality of Passenger Goods Inspection Services at Zainuddin Abdul Madjid Lombok International Airport - Pratiwi, Ega; Awan, Awan (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This research is motivated by safety and comfort during the flight process using the 3S+1C principle (Safety, Security, Service, and Complaint), AVSEC officers are also required to provide services to passengers using the 3S (Smile, Greet, Greeting) method. Based on this, researchers are interested in testing the influence of the performance of the Aviation Security unit on the quality of passenger goods inspection services at Zainuddin Abdul Madjid Lombok International Airport, which was tested partially. The sampling technique used is probability sampling. The data analysis technique in testing this research hypothesis uses a simple linear regression analysis technique. The results of this research show that in the validity and reliability test all variables consisting of performance and service quality are valid and reliable. In the t test, it was found that the Aviation Security Unit performance variable had a partial influence on purchasing decisions. The results of the coefficient of determination test show that the performance variable has an influence on the quality of service to passengers by 48.7%.